Asthma is a risk factor for new onset chronic migraine: Results from the American migraine prevalence and prevention study. Issue 1 (19th November 2015) - Martin, Vincent T.; Fanning, Kristina M.; Serrano, Daniel; Buse, Dawn C.; Reed, Michael L.; Lipton, Richard B.
Abstract : Objectives: To test the hypothesis that in persons with episodic migraine (EM), asthma is a risk factor for the onset of chronic migraine (CM). Background: Migraine and asthma are comorbid chronic disorders with episodic attacks thought to involve inflammatory and neurological mechanisms. Herein, we assess the influence of asthma on the clinical course of EM. Methods: To be eligible for this observational cohort study, AMPP Study participants had to meet criteria for EM in 2008, complete the validated six‐item asthma questionnaire from the European Community Respiratory Health Survey (ECRHS) in 2008, and provide follow‐up data in 2009. Using the ECRHS, we defined asthma as a binary variable (present or absent) based on an empirical cut score and developed a Respiratory Symptom Severity Score (RSSS) based on the number of positive responses (no severity = 0 positive responses, low severity = 1‐2 positive responses, moderate severity = 3‐4 positive responses, high severity = 5‐6 positive responses). Chronic migraine was the primary outcome measure and was defined as those with ≥15 headache days per month on the 2009 AMPP Study survey. We used logistic regression in separate models to assess the influence of asthma as a binary variable (Model 1) and RSSS score categories (Model 2 using no respiratory symptoms as the reference) on CM onset after adjusting for sociodemographic factors, headache day frequency, migraine preventive medication use, and medication overuse. Results: The eligible sample for this study included 4446 individuals with EM in 2008 of whom 17% had asthma. This group had a mean age of 50.4 and was 80.8% female. In 2009, new onset CM developed in 2.9% (131/4446) of the 2008 EM cohort, including 5.4% (40/746) of the asthma subgroup and 2.5% (91/3700) of the non‐asthma subgroup. In comparison to those without asthma, the adjusted odds for individuals with asthma and EM in 2008 to develop CM in 2009 were greater than two (adjusted odds ratio [aOR] 2.1; 95% CI: 1.4‐3.1). Using the RSSS, the aOR for CM onset increased with the number of asthma symptoms, but only those in the high RSSS category showed a statistically significant increase in the odds of chronic migraine onset in comparison with the no RSSS reference group (aOR 3.3; 95% CI 1.7‐6.2). Conclusions: Asthma is associated with an increased risk of new onset CM 1 year later among individuals with EM, with the highest risk being among those with the greatest number of respiratory symptoms. The exact mechanisms underlying this association are unknown, but could suggest mast cell degranulation, autonomic dysfunction, or shared genetic or environmental factors.